Studi Pemeliharaan Fisik pada Kebun Raya Cibinong (KRC), Bogor - Qurrotu ‘Aini Besila; Ovia Syabilla; Etty Indrawati; Titiek P. Debora (Jurnal Lingkungan dan Kota, 2024)
Evaluation of Physical Maintenance at Cibinong Botanical Garden, Bogor. Cibinong Botanical Garden (CBG) is a plant conservation area located on Jl. Raya Jakarta-Cibinong Km.46, Cibinong, Bogor. Cibinong Botanical Garden has become one of the places for educational tours for the people of Cibinong and its surroundings, but based on reviews obtained from Google Maps CBG within one month to ten months after CBG operates, seven of the 36 reviews of visitors who attended gave reviews about maintenance on the minimum number of plants and pavements in CBG, this can be seen from the decrease in the condition of soft materials and hard materials in the garden such as wooden bridges that have holes and rot and dead bush plants that are not replaced by new materials. Implementation of maintenance is very important because it aims to maintain the comfort of visitors and the beauty of the area. This study aims to describe the physical maintenance that takes place at the Cibinong Botanical Garden, to determine the effectiveness of maintenance work at the Cibinong Botanical Garden, and to provide recommendations for physical maintenance as an effort to improve the quality of garden elements in the Cibinong Botanical Garden. The research method used is qualitative with a case study approach. The results obtained from the research are that there is no maintenance schedule that becomes a guideline in carrying out physical maintenance, missed several physical maintenance steps, and there is still a lack of human resources in carrying out maintenance.